IMPLEMENTATION OF TRADITIONAL GAMES WITH MODIFICATIONS IN MATHEMATICS LEARNING FOR EARLY CHILDHOOD - Kholidah, Khasa Aulia; Widjayatri, RR. Deni; Fatihaturosyidah, Fatihaturosyidah; Suzanti, Lizza; Mashudi, Esya Anesty; Tristyanto, Budhi; Nuroniah, Pepi (Unika Santo Thomas Medan, 2023)
The purpose of this study is to cultivate the skill of numbering numbers 1 - 10, and to introduce children to the concept of building space, and children can distinguish large and small sizes through a game of modification of the area Jl. Bojong Raya, Cengkareng, West Jakarta. The method in this study is a qualitative research method with a descriptive approach. The results of the experiment showed that children's skills have improved from achievement indicators Starting to Develop to Developing As Expected in the ability to number numbers 1-10 without having to be guided by researchers and children have been able to distinguish the shape of the size between large and small space buildings, but in terms of recognizing space builds such as balls, beams, and trapezoids of children aged 4-7 years the achievement indicators obtained are from Undeveloped to Starting Flower. The conclusion obtained through this study is that through this modified traditional game, mathematics learning for early childhood is not boring so children's mathematics skills can experience good improvement in accordance with expectations.